# Solve for n p=((m+n)/-5) p=(m+n-5)
Rewrite the equation as m+n-5=p.
m+n-5=p
Multiply both sides of the equation by -5.
-5⋅m+n-5=-5⋅p
Simplify -5⋅m+n-5.
Cancel the common factor of 5.
Factor 5 out of -5.
5(-1)⋅m+n-5=-5⋅p
Factor 5 out of -5.
5⋅-1⋅m+n5⋅-1=-5⋅p
Cancel the common factor.
5⋅-1⋅m+n5⋅-1=-5⋅p
Rewrite the expression.
-1⋅m+n-1=-5⋅p
-1⋅m+n-1=-5⋅p
Simplify the expression.
Move the negative one from the denominator of m+n-1.
-1⋅(-1⋅(m+n))=-5⋅p
Rewrite -1⋅(m+n) as -(m+n).
-1⋅(-(m+n))=-5⋅p
-1⋅(-(m+n))=-5⋅p
Apply the distributive property.
-1⋅(-m-n)=-5⋅p
Apply the distributive property.
-1(-m)-1(-n)=-5⋅p
Multiply -1(-m).
Multiply -1 by -1.
1m-1(-n)=-5⋅p
Multiply m by 1.
m-1(-n)=-5⋅p
m-1(-n)=-5⋅p
Multiply -1(-n).
Multiply -1 by -1.
m+1n=-5⋅p
Multiply n by 1.
m+n=-5⋅p
m+n=-5⋅p
m+n=-5p
Subtract m from both sides of the equation.
n=-5p-m
Solve for n p=((m+n)/-5)

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top